Human-animal interaction as a social determinant of health: descriptive findings from the health and retirement study - Megan K. Mueller; Nancy R. Gee; Regina M. Bures (BMC, 2018)
Abstract Background We focused on human-animal interaction (HAI) as an important aspect of social functioning at the individual level, framing this emerging field from a public health perspective. Methods Using data from the Health and Retirement Study (HRS) 2012 HAI module, we describe the characteristics of pet ownership in a population of older adults, and examine the relation between pet ownership and multiple mental and physical health indicators such as health status, depression, and physical activity. Results Of the 1657 participants in our subsample, approximately half (51.5%) reported being pet owners; the majority owned dogs or cats, and most had only one pet. Pet ownership was significantly associated with a higher likelihood of ever having had depression, with pet owners being 1.89 times more likely to have experienced depression. However, pet ownership was not associated with having experienced depression within the last week. Conclusions The findings from this study could indicate a relationship between pet ownership and depression, but it is impossible to determine the directionality of that relationship. It is possible that owning a pet may put a person at an increased risk of developing depression, or individuals who are at risk, or who have already developed depression, may acquire a pet as a way of managing their depressive symptoms. The findings of this study provide an initial step in contributing to our understanding of the relationship between companion animals and the social, physical, and mental well-being of the HRS study population. Future research should include measures of HAI in longitudinal, population-based surveys.